2010
DOI: 10.1080/07317115.2010.502103
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Well-Being and Self-Rated Health Among Middle-Aged and Older Women in Israel

Abstract: Self-rated health (SRH) is widely used to assess global health. This study evaluated the SRH of two groups of women aged 40 to 59 and 60+ years. In a sample ( n = 306), from a random telephone survey, variables reflecting sociodemographic status, subjective well-being, and health were examined to explain SRH. The results showed that the two groups differed significantly on measures of subjective well-being, as well as in number of comorbidities and level of disability. Two hierarchical regression analyses show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 36 publications
4
18
0
1
Order By: Relevance
“…It was uncommon for participants to select the top or bottom category in any of the measures, therefore the bottom two and top two categories were collapsed. Self-perceived health at older ages has been shown to be influenced by emotional wellbeing and physical health and is strongly correlated with objective health measures (Iecovich and Cwikel, 2010). Research suggests perceived life satisfaction reflects continuing long-term life circumstances, whilst perceived happiness has a closer link to emotions and reflects short-term current status (Helliwell and Barrington-Leight, 2010).…”
Section: Wellbeingmentioning
confidence: 97%
“…It was uncommon for participants to select the top or bottom category in any of the measures, therefore the bottom two and top two categories were collapsed. Self-perceived health at older ages has been shown to be influenced by emotional wellbeing and physical health and is strongly correlated with objective health measures (Iecovich and Cwikel, 2010). Research suggests perceived life satisfaction reflects continuing long-term life circumstances, whilst perceived happiness has a closer link to emotions and reflects short-term current status (Helliwell and Barrington-Leight, 2010).…”
Section: Wellbeingmentioning
confidence: 97%
“…Researchers who have described how women experience aging differently than men contribute a rationale for examining older women's resilience and identify aspects of identity that shape older women's experiences with aging and adversity. Older women's longevity contributes to an increased likelihood of experiencing health problems and a result, older women are more likely to suffer from stroke and hypertension, have functional limitations, report lower self-rated health [18,19] and more chronic health conditions [2] than their male counterparts. With respect to psychological health, older women are more likely to be diagnosed with anxiety, depression and post-traumatic stress disorder and more likely to take psychotropic medications than men [20].…”
Section: Women's Aging and Identity Factorsmentioning
confidence: 99%
“…Researchers who have studied older women's resilience have also focused critiques on the limited identities represented in study samples and have recommended that future research on older women's resilience examine how resilience varies according to identity differences such as gender, age, ethnicity, health, income, and geographic location [16][17][18][19] Although disability scholars focused on health and mobility, we considered the role of multiple other identity factors and how they contributed to women's experiences with adversity and resilience.…”
Section: Defining Resiliencementioning
confidence: 99%
See 1 more Smart Citation
“…In addition, we asked about general health using a 5-point self-rated health variable that based on earlier research has been shown to be associated with depressive symptoms and functional health status among Israeli women of a similar age to this sample (Iecovich & Cwikel, 2010).…”
Section: Methodsmentioning
confidence: 99%